The Influence of Exercise Intensity on Postexercise Baroreflex Sensitivity. Issue 1 (2nd January 2017) - Reynolds, Linda J.; De Ste Croix, Mark B. A.; James, David V. B.
Abstract : Purpose: The purpose of this study was to investigate the influence of exercise intensity on postexercise supine and tilt baroreflex sensitivity (BRS).Method: Nine healthy, active men performed 2 conditions of interval cycling of 40% maximal work rate (WRmax ) and 75% WRmax of matched work done and a control condition of no exercise in a counterbalanced order. BRS outcome measures were determined at preexercise and postexercise up to +24 hr in supine and tilt positions. R-R interval and blood pressure data were collected over consecutive 10-min periods and were analyzed by Fast Fourier transformation analysis.Results: A fully repeated analysis of variance revealed a significant interaction ( p  < .05) between time and condition in supine for BRSαLF, F (3, 134) = 5.19, p  < .05, ES = .39, and BRSTFTG, F (3, 134) = 5.65, p  < .05, ES = .41, and in tilt for BRSUpUp, F (3, 134) = 3.54, p  < .05, ES = .31, BRSDownDown, F (3, 134) = 5.94, p  < .05, ES = .43, BRSαLF, F (4, 134) = 6.23, p  < .05, ES = .44, and BRSTFTG, F (4, 134) = 9.22, p  < .05, ES = .54. There were significant differences ( p  < .05) between condition comparisons at +15 min and between control and 75% WRmax and between the 40% WRmax and 75% WRmax conditions at +60 min. At +15 min, BRS was lower in the 75% WRmax condition compared with the 40% WRmax condition and the control condition, and it was lower in the 40% WRmax condition than in the control condition.Conclusion: The findings demonstrate an intensity-dependent relationship in the BRS response following exercise.